ABN AMRO : activist shareholders among the hedges (B) - Maduro, Lorena; Paunescu, Anca; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
On February 20, 2007, The Childrens Investment Fund sent a letter to the board of Dutch bank ABN AMRO requesting that ABN AMRO explore options to merge, sell, or spin-off some of its assets, or even the whole business. Never before had shareholder activism reached such a scale. As turmoil reigned and speculation began, the largest bidding war in banking history began over one of Europes largest and oldest banks.
Originally published: Maduro, L., Paunescu, A., & ORourke, J. S. (2008). ABN AMRO: Activist shareholders among the hedges (B). 08-01 (B). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; ABN AMRO Bank; Banks and banking -- Netherlands; Liquidation -- Netherlands; Consolidation and merger of corporations -- Netherlands; Corporate governance -- Netherlands